Tobacco smoking associated with adverse childhood experiences in a Brazilian community university sample: A case-control study. (January 2021) - Maia-Silva, Keyla Medeiros; Zamel, Noe; Selby, Peter; Fontes, Cor Jesus Fernandes; Santos, Ubiratan Paula
Highlights: The prevalence of smoking was associated with adverse childhood experiences. Smokers had a higher number of compromised ACE scales. There was a higher prevalence of all ACE scales among smokers. The level of tobacco dependence was correlated with the score of ACE. ACE favors low self-esteem and chemical dependency. Abstract: Background: Adverse childhood experiences have been shown to have a great impact on adult health and social outcomes including tobacco smoking. Studies have shown this association but were mainly conducted in the USA. Objective: To evaluate the association between smoking, general characteristics, and adverse childhood experiences in a population of a Brazilian University. Participants and setting: Population formed by students and employees of a Brazilian University. Case-control observational study with a 1: 1 pairing by age, sex and education. The cases were defined as participants using nicotine-containing products, whether from burnt or unburned tobacco or electronic cigarettes, and the controls never users. Methods: We conducted the study using a Portuguese translation of the brief version of the family background questionnaire (8 adverse childhood experiences categories) in a group of 1056 participants with mean age of 31 years of a university community in Brazil. Smokers were compared to non-smokers on their adverse childhood experiences scores. Results: The prevalence of smoking in adulthood was significantly associated with the score of adverse childhood experiences. In addition, the level of tobacco dependence in adulthood also correlated with the score of adverse childhood. Conclusions: The association, including a possible dose-response relationship, in young adults between adverse childhood experiences and smoking was confirmed in a population of a Brazilian university. This further adds to our understanding of the determinants of adult tobacco use in a relatively more diverse cosmopolitan scenario.